2021
DOI: 10.12688/digitaltwin.17435.1
|View full text |Cite
|
Sign up to set email alerts
|

Digital twins and their use in future power systems

Abstract: The electric power sector is one of the later sectors in adopting digital twins and models in the loop for its operations. This article firstly reviews the history, the fundamental properties, and the variants of such digital twins and how they relate to the power system. Secondly, first applications of the digital twin concept in the power and energy business are explained. It is shown that the trans-disciplinarity, the different time scales, and the heterogeneity of the required models are the main challenge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 59 publications
0
14
0
Order By: Relevance
“…In this paper various kinds of faults in the PV panels are considered. In [38], a monitoring system based on DT is proposed to predict the faults in a physical power converter within the digital model is entrenched by a controller. In [39], a digital model of a power system is proposed to trace the dynamic faults of voltage and also forecast the dynamic behavior of the post-fault.…”
Section: ) Management and Monitoringmentioning
confidence: 99%
“…In this paper various kinds of faults in the PV panels are considered. In [38], a monitoring system based on DT is proposed to predict the faults in a physical power converter within the digital model is entrenched by a controller. In [39], a digital model of a power system is proposed to trace the dynamic faults of voltage and also forecast the dynamic behavior of the post-fault.…”
Section: ) Management and Monitoringmentioning
confidence: 99%
“…3) The digital twin concept, a virtual replica of a physical MES, enables testing and experimenting the impact of integration of new technology and strategy [103]. The MLBTs can be embedded in the digital twin to simulate the MES operation in various extreme events, and to develop and verify the resilience assessment and enhancement methods.…”
Section: B Future Directions Of Mlbts Applied To Mes Resilience Asses...mentioning
confidence: 99%
“…(Rasheed et al, 2019) reported the challenges, methodologies and techniques related to the development of digital-twins. (Palensky et al, 2021) reported the history of digital-twins, fundamental properties and how digital-twins are related to different power systems. Other studies (Huang et al, 2021;Onile et al, 2021;Pan et al, 2020;Xu et al, 2019) have reported the application of digital-twins within power systems.…”
Section: Introductionmentioning
confidence: 99%
“…(Palensky et al, 2021) reported the history of digital-twins, fundamental properties and how digital-twins are related to different power systems. Other studies (Huang et al, 2021;Onile et al, 2021;Pan et al, 2020;Xu et al, 2019) have reported the application of digital-twins within power systems. In a previous study (Panov and Cruz-Manzo, 2020), a gas turbine real-time executable digital-twin (RT xDT) was reported.…”
Section: Introductionmentioning
confidence: 99%